Contradiction Of Using Hujjah With Daif Hadith In Fadail A'mal: Analysis of the Book of Al-Targib wa al-Tarhib - Anisah, Rafiqatul; Afabih, Abdillah (Al-Bukhari : Jurnal Ilmu Hadis, 2023)
Scholars of hadith have mentioned that da'if (weak) hadiths can be used for Fadail Al-A'mal (virtuous actions), but it is uncertain which type of da'if hadith can be used as evidence. Although previous researchers have conducted numerous studies on this topic, this paper aims to discuss the validity of using da'if hadiths as evidence for Fadail al-a'mal by examining the types, conditions, and replacement hadiths of da'if narrations. The conclusions presented in this paper are based on the opinions of hadith scholars, taking into account both the advantages and disadvantages. The researcher employs an analytical study method, focusing on the da'if hadiths compiled in the book "Targhib wa At-Tarhib" in the chapter on Thaharah (purification). The findings of this study indicate that Syadid al-da'ifi refers to a category of hadith that cannot be rectified. Within the Thaharah chapter of the Kitab At-Targhib and At-Tarhib, there are 118 hadiths categorized as follows: 43 authentic hadiths, 16 hasan (good) traditions, 7 da'if traditions, and 52 traditions for which al-Hafizh al-Mundhiri (the author of the book) does not mention their authenticity. Researchers have attempted to identify da'if hadith substitutes to remove the prohibition on using da'if hadiths as evidence for Fadail Al-A'mal. Consequently, out of the seven hadiths, five da'if hadiths can be replaced. The first, third, fourth, and sixth hadiths, however, do not require replacement as they are not weak.